Unemployment, firm dynamics, and the business cycle - Andrea Colciago; Stefano Fasani; Lorenza Rossi (Queen Mary University of London, School of Economics and Finance, 2020)
We formulate and estimate a business cycle model which can account for key business cycle properties of labor market variables and other aggregates. Three features distinguish our model from the standard model with Search And Matching (SAM) frictions in the labor market: frictional firm entry, endogenous product variety, and investment in two assets: stocks and physical capital. Our model with firm dynamics displays an endogenous form of wage moderation. Thanks to the latter, it outperforms the SAM framework augmented with exogenous real wage rigidities.
Keywords: C5; E32; 330; Entry; Unemployment; Bayesian Analysis; Search and Matching